Model for calculating apar reliability indicators by the criterion of permissible reduction of the maximum radar range - Костановский, Валерий Вікторович; Мачалін, Ігор Олексійович; Демченко, О. В.; Козачук, Оксана Дмитрівна (Science-based technologies, 2020)
The purpose of this article was to develop a model for calculating APAR reliability indicators by the criterion of an acceptable reduction in the maximum radar range. The radar range equation relates the maximum range of the radar and its parameters: power emitted by the APAR, transmit antenna gain, receive antenna gain. During the operation of the APAR, its active elements gradually fail: the transmitting and receiving channels of the transceiver modules of the sublattices and the AFAR as a whole, as well as the secondary power supply modules. This leads to a decrease in radiated power and a decrease in gain. The number of failures of transmission channels and power supply modules is determined by their failure rates and the total number of channels and modules. Using the formula of radar, as well as the dependence of the decrease in radiated power and amplification factors on the number of failed transmitting and receiving channels of the AFAR, the analytical dependence of reducing the maximum range of the radar from the mean time to failure of the radar was determined. In general form (with an arbitrary law of distribution of failures of transmitting, receiving channels and power supply modules), this dependence is a transcendental equation with respect to the mean time between failures of the AFAR. Using the exponential distribution of failures and expanding the exponent in a series of two terms, the transcendental equation was able to be converted into an approximate formula for determining the mean time between failures and the failure rate of AFAR. The article also presents an illustrative example of calculating reliability indicators: mean time to failure and failure rate, depending on the allowable decrease in the maximum radar range. The graphs of the dependence of the average operating time to failure on the values ​​of the allowable decrease in the maximum range and failure rates of the transmitting channels and power supply modules are presented. The results presented in the article are recommended to be used to assess the reliability of AFAR during the design and operation of radars.